STUDIES OF THE WORKING CAMERA OF THE LINTER - Mahmudov Yu. A. (European Journal of Interdisciplinary Research and Development, 2022)
The article analyzes the existing UMPL and creates a base for theoretical and experimental studies of a new working chamber with high performance and stability of operation, ensuring safety and reducing energy intensity.